2020
DOI: 10.1007/s42860-020-00088-4
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Structural Properties of Clay Materials Based on Natural Saponite

Abstract: Because they are so widespread, the use of saponites is significant in many industries. The modification of saponite-rich clay minerals is known to improve their existing characteristics and may provide new functional properties. The objective of the present paper was to characterize the effects of adding nanosized graphene-like molybdenum (Mo) and tungsten (W) sulfides on the textural and surface characteristics of composites based on native saponite and saponite pre-modified with nanoscale magnetite. The tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The other possible factor is a pH change on the saponite surface. It was reported that saponite surfaces are weakly acidic, , and the effect of pH on the MQu + equilibrium was examined at pH = 2, 3, and 6. As can be seen in Figure S12, the absorption spectra of MQu + did not depend on pH at all.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The other possible factor is a pH change on the saponite surface. It was reported that saponite surfaces are weakly acidic, , and the effect of pH on the MQu + equilibrium was examined at pH = 2, 3, and 6. As can be seen in Figure S12, the absorption spectra of MQu + did not depend on pH at all.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Many studies have been reported on the unique effects of the interface between a saponite surface and an aqueous solution. Our group has reported unique phenomena of adsorbed species on a saponite surface. , For example, the emission enhancement of adsorbed species and photoisomerization control on the saponite surface have been reported. These examples can be interpreted mainly as steric effects of the saponite surface on “intra”-molecular reactions and processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural saponite is a very unique modifier, saponite nanoparticles have great specific surface area, surface free energy, high mechanical strength and reinforcing capacity. 17,18 However, the large number of hydroxyl groups on the surface of saponite makes it extremely hydrophilic and prone to agglomeration, thus limiting its use in hydrophobic polymer matrices, and it can lead to the formation of stress concentrations resulting in poor reinforcement. 19 To overcome these challenges, several researchers have performed various modifications to saponite, not only retaining the advantages of PLA itself, but also giving it new functions.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of PLA can be further enhanced by the addition of various inorganic nanoparticles such as fibers, 12 hydrotalcite, 13 hydroxyapatite, 14 bumpy rods, 15 calcium carbonate, 16 etc., aiming to enhance the various properties of PLA to broaden its applications. Natural saponite is a very unique modifier, saponite nanoparticles have great specific surface area, surface free energy, high mechanical strength and reinforcing capacity 17,18 . However, the large number of hydroxyl groups on the surface of saponite makes it extremely hydrophilic and prone to agglomeration, thus limiting its use in hydrophobic polymer matrices, and it can lead to the formation of stress concentrations resulting in poor reinforcement 19 .…”
Section: Introductionmentioning
confidence: 99%